2009
DOI: 10.1029/2009gl038340
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer modeling to interpret the spin state of iron in (Mg,Fe)SiO3 perovskite

Abstract: [1] The properties of (Mg,Fe)SiO 3 perovskite at lower mantle conditions are still not well understood, and particular attention has recently been given to determining the Fe spin state. A major challenge in spin states studies is interpretation of Mössbauer spectra to determine the electronic structure of iron under extreme conditions. In this paper ab initio methods are used to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
67
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 44 publications
4
67
0
Order By: Relevance
“…These signatures have been widely reported in previous seismic tomography studies such as the disruption of P wave image below some hot spots (Zhao, 2007), the global disruption of P wave structure (van der Hilst and Kárason, 1999) at ∼1700 km depth, anti-correlation between shear velocity and bulk sound velocity around middle lower mantle (Simmons et al, 2010), and discrepancy between P and S wave model at the origin depth of thermal plumes (Boschi et al, 2007). Here we further found that iron-spin transition may control the formation of LLSVPs, a signature of the spin transition from geodynamic aspect.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…These signatures have been widely reported in previous seismic tomography studies such as the disruption of P wave image below some hot spots (Zhao, 2007), the global disruption of P wave structure (van der Hilst and Kárason, 1999) at ∼1700 km depth, anti-correlation between shear velocity and bulk sound velocity around middle lower mantle (Simmons et al, 2010), and discrepancy between P and S wave model at the origin depth of thermal plumes (Boschi et al, 2007). Here we further found that iron-spin transition may control the formation of LLSVPs, a signature of the spin transition from geodynamic aspect.…”
Section: Discussionmentioning
confidence: 83%
“…Iron in bridgmanite is more complex than iron in Fp: it can exist in Fe 2+ and Fe 3+ states and can occupy the A site and B site. First-principles calculations show that the extremely high quadruple splitting value of Fe 2+ in bridgmanite above ∼30 GPa, which has been interpreted as the high-spin to the intermediate-spin transition (Lin et al, 2008;McCammon et al, 2008), results from the change of local structure of A site Fe 2+ (Bengtson et al, 2009;Hsu et al, 2011), whose effect on density and bulk modulus are much smaller than the effect of spin transition on density and bulk modulus of ferropericlase (Lundin et al, 2008). The experimental and theoretical studies show that only B site Fe 3+ experiences high spin to low spin transition at lower mantle pressure (Stackhouse et al, 2007;Hsu et al, 2011;Fujino et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, spin crossover in Fe-Pv, the major lower-mantle mineral phase, has been highly controversial [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], due to the complex nature of this mineral. In addition to Fe [32,33], a consensus has gradually been reached: only Fe 3+ residing in the B site undergoes a crossover from HS (S = 5/2) to LS (S = 1/2) state; iron in the A site remains in HS state, regardless of its oxidation state.…”
mentioning
confidence: 99%
“…For HS to IS, the changes would be expected to be smaller because of the smaller difference in Fe 2+ radii. A contrasting view comes from computational studies designed both to predict the form of spinstate variations and to test interpretations of Mössbauer spectra (e.g., Hofmeister 2006;Zhang and Oganov 2006;Stackhouse et al 2007;Bengtson et al 2008Bengtson et al , 2009Umemoto et al 2008Umemoto et al , 2010Hsu et al 2010Hsu et al , 2011. According to Hsu et al (2011) these were not consistent with the experiments until Hsu et al (2010) showed that the observed changes in quadrupole splitting are not due to any spin transition but rather to a change of configuration of HS Fe 2+ within the A site.…”
mentioning
confidence: 88%
“…There has been some controversy in relation to the nature of the stable spin configuration of Fe 2+ at high pressures and temperatures (Li et al 2004(Li et al , 2006Badro et al 2004;Jackson et al 2005;McCammon et al 2008;Bengtson et al 2009;Umemoto et al 2010;Hsu et al 2010), but recent experimental work has been interpreted as indicating that the HS state, stable at ambient conditions, gives way to an increasing population of intermediate-spin (IS) states with increasing pressure between ~30 and 65 GPa Narygina et al 2009Narygina et al , 2010. High temperatures would * E-mail: zhiyingzhang06@hotmail.co.uk favor the IS state and the expectation might therefore be that Fe 2+ is predominantly IS throughout the lower mantle, with variations in the uppermost part and in cold subducted slabs .…”
mentioning
confidence: 99%